Performance Analysis of the Regional Public Service Agency (BLUD) of the Tanara Health Center, Serang Regency using the Balance Scorecard Approach - Wina Andryani; Fibria Indriati (Asian Journal of Social and Humanities, 2024)
This study aims to analyze the performance of the Regional Public Service Agency (BLUD) at the Tanara Community Health Center in Serang Regency using the Balance Scorecard approach. The Balance Scorecard emphasizes the importance of balancing various aspects such as financial and non-financial, short-term and long-term, as well as internal and external factors. The performance analysis of the BLUD is viewed from four perspectives: growth and learning, internal processes, customer satisfaction, and financial perspectives. This research adopts a quantitative approach. Data collection is conducted through surveys to gather insights into the growth and learning perspective, the internal process perspective, and the customer satisfaction perspective. Secondary data is used to analyze the BLUD's performance from the financial perspective. The results of this study indicate that the health center has not yet met the target scores set by the government. Although some indikators have been achieved, there is still a need for improvement, particularly in internal processes and customer satisfaction. To enhance the performance of the BLUD at this health center, integrated efforts are required, such as improving services and internal processes as well as fostering innovation.